Using deep eutectic solvent pretreatment for enhanced enzymatic saccharification and lignin utilization of masson pine. (August 2022) - Yang, Luan; Zheng, Tianran; Huang, Chen; Yao, Jianfeng
Abstract: Bioconversion of renewable biomass into various useful chemicals is considered as the main way to achieve low-carbon development. Here, efficient conversion of masson pine was realized through biological refining as follows: using deep eutectic solvent (choline chloride/lactic acid) pretreatment to remove lignin and degrade hemicellulose; adding UiO-66-NH2 to boost enzymatic hydrolysis yield; and reusing extracted lignin to prepare a functional material. The effects of pretreatment conditions on enzymatic hydrolysis and the purity of the regenerated lignin were studied. Under the optimal condition (130 °C, 1:10, 4 h), lignin removal rate, lignin recovery, and the purity of the recovered lignin were 81.2%, 72.3%, and 92.5%, respectively. The hydrolysis yield of cellulose at 5 FPU/g-glucan enzyme dosage was increased from 42.1% to 52.8% after using UiO-66-NH2 . The regenerated lignin was further utilized to synthesize an ultraviolet shielding film. In short, this work can achieve efficient utilization of all components of masson pine. Graphical abstract: Image 1 Highlights: The full utilization of masson pine can be realized. Deep eutectic solvents pretreatment can remove and extract high purity lignin. The addition of metal organic frameworks achieves efficient conversion of cellulose. Role of MOFs in improving enzymatic hydrolysis of masson pine is discussed.